Critical Mass of What? Exploring Community Growth in WikiProjects - Solomon, Jacob; Wash, Rick (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
Fledgling online communities often hope to achieve critical mass so that the community becomes sustainable. This concept however is not well understood. At what point does a community achieve critical mass, and how does the community know this? Furthermore, online communities become sustainable when they achieve a mass of what? We explore this question by analyzing growth in a large number of online communities on Wikipedia. We find that individual communities often have different patterns of growth of membership from its pattern of growth of contribution or production. We also find that in the early stages of community development, building membership has a greater impact on community production and activity in later periods than accumulating many contributions early on, and this is especially true when there is more diversity in the early participants in a community. We also show that participation from a community’s "power users" in its early stage is not as valuable to sustainability as the collective contributions of those who make only small contributions. We argue that critical mass is established by developing a diverse set of community members with heterogeneous interests and resources, and not purely by accumulating content.